2013
DOI: 10.1186/1475-2867-13-92
|View full text |Cite
|
Sign up to set email alerts
|

Three steps to the immortality of cancer cells: senescence, polyploidy and self-renewal

Abstract: Metastatic cancer is rarely cured by current DNA damaging treatments, apparently due to the development of resistance. However, recent data indicates that tumour cells can elicit the opposing processes of senescence and stemness in response to these treatments, the biological significance and molecular regulation of which is currently poorly understood. Although cellular senescence is typically considered a terminal cell fate, it was recently shown to be reversible in a small population of polyploid cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(177 citation statements)
references
References 138 publications
(260 reference statements)
10
166
0
1
Order By: Relevance
“…Neosis is considered as occurring in multinucleated postsenescent cells and as being characterized by karyokinesis via nuclear budding and asymmetric cytokinesis, producing aneuploid mononuclear cells with extended lifespans and transient stem cell features. It is believed that polyploid mother cells die after these events (Rajaraman et al, 2006;Erenpreisa and Cragg, 2013). Consequently, genotoxic resistance seems to be closely associated with reversible senescence, polyploidization, and stemness.…”
Section: Introductionmentioning
confidence: 99%
“…Neosis is considered as occurring in multinucleated postsenescent cells and as being characterized by karyokinesis via nuclear budding and asymmetric cytokinesis, producing aneuploid mononuclear cells with extended lifespans and transient stem cell features. It is believed that polyploid mother cells die after these events (Rajaraman et al, 2006;Erenpreisa and Cragg, 2013). Consequently, genotoxic resistance seems to be closely associated with reversible senescence, polyploidization, and stemness.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is reasonable to suggest that the unique mechanism of acquired resistance to metformin has opposing roles in growth and metastatic dissemination, while refractoriness to metformin limits breast cancer cell growth, likely due to an aberrant mitotic/cytokinetic machinery and accelerated autophagy, it notably increases the potential of metastatic dissemination by amplifying the number of pro-migratory and stemness inputs via the activation of a significant number of proteases and EMT regulators. Future studies should unambiguously elucidate whether our findings using supra-physiological concentrations of metformin mechanistically recapitulate the processes through which the induction of a migratory-stemness cellular state paradoxically occurs in a polyploid, senescent-autophagic scenario [102][103][104][105] that is triggered by the chronic metabolic stresses that commonly occur during cancer development and after treatment with cancer drugs.…”
Section: P Value Ratiomentioning
confidence: 99%
“…This is no surprise given the range of evolutionary trajectories that characterize diverse cancer types and the difficulty of obtaining a truly representative picture of the evolutionary paths that cell lineages follow within a single tumor (Gerlinger et al 2014b;Walther et al 2015). Beyond the unresolved population genetic considerations of the effects of variation in a polyploid context (e.g., see Otto and Whitton 2000;Gerstein and Otto 2009), on the phenotypic side, recent work suggested that polyploidy may indeed promote rampant aneuploidy and genetic and phenotypic diversity (Lagadec et al 2012;Erenpreisa and Cragg 2013;Zhang et al 2013). Furthermore, polyploid giant cells, which are often found in human solid tumors, are highly resistant to low oxygen conditions, cycle slowly (Zhang et al 2013), and have been proposed to also contribute to lineage expansion and heterogeneity upon induction by chemotherapy or radiation treatment (Lagadec et al 2012;Zhang et al 2013).…”
Section: Mammalsmentioning
confidence: 99%